(untitled) (Baghdad Science Journal, 2015)
A new ligand 2,3-dihydrobenzo [d] thiazole-2-carboxylic acid (L) has been prepared from the reaction of ortho amino phenyl thiol with dichloroacetic acid in mole ratio (1:1). It has been characterized by elemental analysis (C.H.N.), IR, UV- Vis.spectraand 1H, 13C-NMR. A new series complexes of the bivalent ions (Co, Ni, Cu, Pd, Cd, Hg and Pb) and the trivalent (Cr) have been prepared and characterized too. The structural has been established by elemental analysis (C.H.N.), IR, UV-Vis. spectra, molar conductivity, atomic absorption and magnetic susceptibility measurements. The synthesized complexes were prepared in (1:2) ratio correspond to (Co(II), Ni(II), Cu(II), Pd(II), Cd(II), Hg(II) and Pb(II) complexes while in case Cr(III) complex is (1:1) ratio (M:L). ?, Kf for (Cr(III), Co(II), Ni(II) and Cu(II)) were estimated too. The complexes showed characteristics octahedral geometry with the (O,N) ligand coordinated in bidentate mode except with Pd showed square planer. The study of biological activity of ligand (L) and its complexes showed various activities toward Staphylococcus aureusand E. coli.